Fine-tuning calibration of deterministic propagation models in UHF band. (April 2019) - Militaru, G; Popescu, D; Ichim, L
Abstract: A global characterization of the propagation behaviour that will allow a general approach of the Radio Frequency (RF) prediction is difficult to achieve. In this paper, based on field strength values collected in typical rural environment, the authors are providing their findings after the calibration of a deterministic propagation model in Ultra High Frequency (UHF) frequency band. An evaluation of the error sources, and methods to validate RF antenna pattern, are described. The proposed methodology was used to obtain the measurements that allow the correlation with prediction data.